Introduction to circuit analysis and design - Glisson, Tildon H.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Introduction to Circuit Analysis and Design takes the view that circuits have inputs and outputs, and that relations between inputs and outputs and the terminal characteristics of circuits at input and output ports are all-important in analysis and design. Two-port models, input resistance, output impedance, gain, loading effects, and frequency response are treated in more depth than is traditional. Due attention to these topics is essential preparation for design, provides useful preparation for subsequent courses in electronic devices and circuits, and eases the transition from circuits to systems.The differences in depth of treatment arise from a focus on teaching analysis as preparation for design, where the devil is in the details. Introduction to Circuit Analysis and Design gives due attention to differences between physical circuits or devices and circuit or device models, including variation of resistance and capacitance with temperature, variation of resistance with frequency, parasitic and stray capacitance and inductance, residual effects such as leakage resistance of capacitors and winding resistance of inductors, and other such things either not covered or barely mentioned in other books. The treatment of operational amplifiers goes well beyond the ideal model, covering topics such as gain-bandwidth product, slew rate, bias-current compensation, output swing, and power dissipation, all of which must be considered in any realistic design. Where appropriate, chapters conclude with a section that discusses implications for and applications to design.
Electronic reproduction .
Keywords: Electronic books; Electric circuits